Tuned Aperture Computed Tomography (TACT®) for Cross-Sectional Implant Site Assessment in the Posterior Mandible - Behnoush Rashedi, DMD, MS,1 Donald A. Tyndall, MPH, DDS, PhD,2 (Journal of Prosthodontics, 2003)
This study was designed to optimize a new radiographic modality known as tuned aperture computed tomography (TACT) for cross-sectional imaging of implant sites in human dry mandibles.